Political connections and psychosocial wellbeing among Women's Development Army leaders in rural amhara, Ethiopia: Towards a holistic understanding of community health workers' socioeconomic status. (December 2020) - Closser, Svea; Maes, Kenneth; Gong, Erick; Sharma, Neha; Tesfaye, Yihenew; Abesha, Roza; Hyman, Mikayla; Meyer, Natalie; Carpenter, Jeffrey
Abstract: Little empirical research exists on the effects of health work on Community Health Workers' (CHWs') social relationships and status, yet these factors are important in understanding the broad social and behavioral drivers and impacts of CHW programs. This is particularly true for unpaid CHWs. Engaging with others as a CHW might help a worker to embody a valued role in society as a selfless, caring individual; or it might strengthen bonds with others and improve social networks and social capital. By combining qualitative, ethnographic, and survey data collected in rural Amhara, Ethiopia from 2013 to 2016, we evaluated the extent to which unpaid female workers in Ethiopia's Women's Development Army (WDA) were better able than their peers to achieve cultural consonance by building desired social connections or fulfilling locally salient models of virtuous womanhood. We conducted a cultural consensus survey (n = 74) and measured cultural consonance in a larger survey of adult women, including WDA leaders (n = 422). We also conducted participant observation and interviews with health officials, local health staff, and WDA leaders. In our study site, WDA leaders were more able than other women to fulfill the cultural ideal of having connections to various government officials. Yet these connections often did not lead to the benefits that WDA leaders hoped for. Also, in contrast to the findings of many other studies, achieving greater cultural consonance was not significantly associated with reduced psychological distress in this population. For women in this rural context, meanwhile, psychological distress is strongly associated with food and water insecurity, stressful life events, and social support. These findings point to the importance of social, economic and psychological support for rural women in Amhara, and specifically for unpaid CHWs. Highlights: We investigated whether unpaid CHW positions provide social benefits to CHWs themselves. Unpaid CHWs in Ethiopia had stronger connections to government officials than other women. Unpaid CHWs were not better able than other women to help their neighbors in socially desired ways. Connections to government officials did not lead to material benefits for most impoverished CHWs. CHWs had high levels of psychological distress associated with poverty and lack of social support.